On Quasi-Conformally Flat Almost Pseudo Ricci Symmetric Manifolds - Shaikh, A. A.; Bagewadi,C. S.; Hui, S. K.
The object of the present paper is to study quasi-conformally flat almost pseudo Ricci symmetric manifolds.
Keywords: Pseudo Ricci symmetric manifold; Almost pseudo Ricci symmetric manifold; Scalar curvature; Conformally flat